Um olhar para o consumo de moda na Vila Madalena (SP) e sua relação com a moda - Nunes, Luisa da Conceição (2014)
Fashion is a social science that pervades the lives of all people. So many have difficulty perceive it as such. It is not developed without a theoretical basis, for all its dynamics is linked to the economic, social, political and cultural issues. This study aims to correlate fashion, culture and city, more precisely an analysis of fashion consumption in the Vila Madalena neighborhood in São Paulo (SP), and consequently the concept in relation with fashion. To this end, studies will be conducted bibliographic and field research. Then, the relationship between these parties will know their interference in the fashion field, producing pieces of garments referring the characteristics of the neighborhood, encouraging their patrons belonging to this part of town.